Folic Acid Conjugated Nanocarriers for Efficient Targetability and Promising Anticancer Efficacy for Treatment of Breast Cancer: A Review of Recent Updates - Choudhury, Hira; Pandey, Manisha; Wen, Lee P.; Cien, Ling Kah; Xin, Ho; Yee, Alvina N. J.; Lee, Ng Joo; Gorain, Bapi; Amin, Mohd Cairul Iqbal Mohd; Pichika, Mallikarjuna Rao (Current Pharmaceutical Design, 2020)
Breast cancer (BC) is the commonest cause of cancer deaths among Women. It is known to be caused due to mutations in certain receptors, viz. estrogens or progesterones. The most frequently used conventional treatment strategies against BC include chemotherapy, radiation therapy, and partial or entire mastectomy, however, these strategies are often associated with multiple adverse effects, thus reducing patient compliance. Advancement of nanotechnology in the medical application has been made to enhance the therapeutic effectiveness with a significant reduction in the unintended side-effects associated with incorporated anticancer drugs against cancer. The surface engineering technology of the nanocarriers is more pronounced in delivering the therapeutics specifically to target cells. Consequently, folic acid, a small molecular ligand for the folate receptor overexpressed cells, has shown immense response in treating BC cells. Folic acid conjugated nanocarriers have shown remarkable efficiency in targeting overexpressed folate receptors on the surface of BC cells. Binding of these target-specific folate-conjugated nanocarriers substantially improves the internalization of chemotherapeutics in BC cells, without much exposing the other parts of the body. Simultaneously, these folate– conjugated nanocarriers provide imaging for regular monitoring of targeted drug delivery systems and their responses to an anticancer therapy. Therefore, this review demonstrates the potential of folate-conjugated nanotherapeutics for the treatment and theranostic approaches against BC along with the significant challenges to anticancer therapy, and the prospective insights into the clinical importance and effectiveness of folate conjugate nanocarriers.
Keywords: folic acid conjugation